ASEAN Policies towards the US-China Relationship during the Covid-19 Pandemic: English - Purwanti, Asih (Interaktif : Jurnal Ilmu-Ilmu Sosial, 2023)
The relationship between the US, China, and ASEAN as regional cooperation covers a wide range of aspects of international relations. Although the aspect of security and finance are considered as traditionally the largest aspect of the cooperation. In 2020, the Covid-19 pandemic brings one more aspect to this relationship. The covid-19 pandemic is also showing the rivalry between two major powers now, China and the United States. The question is then where ASEAN will stand in this contestation. The US has been playing a role as a crucial partner for ASEAN and its member states, but in recent decades, some people argue that ASEAN is growing more preference to China. Some argue that the historical, cultural, and geographical proximity led ASEAN members to be close to China, others argue that Chinese financial and investment supports are more accessible than the ones from the Western world including the US. Some argue that ASEAN is openly embracing Chinese influence in the region because China does not bother with any issues regarding human rights, something that ASEAN member states’ government are reluctant to deal with. For ASEAN, under the mixture of the situation of China-US rivalry, the global pandemic, and domestic problems that occurred in each member states, what should ASEAN do? How the pandemic weighs in the US-China-ASEAN relationship? This study is examining the policies of ASEAN regarding the rivalry between the US and China during the time of the Covid 19 pandemic. I argue that ASEAN will not move away from its original position to stay neutral. And at the same time, ASEAN will also apply the non-interference policies toward its member states to conduct their own bilateral relations with the US and China. These policies are also applied for their policies regarding Covid-19 vaccines. Most ASEAN member states are buying Covid-19 vaccines from China. This study limits the examination only from the perspectives of ASEAN as regional cooperation and ASEAN member states toward US-China dynamics relations during the pandemi. Keywords: ASEAN, US-Chine Relations, Covid-19